Correlation of priority lines of personality with the level of motivation of schoolboys to the specially organized motive activity, depending on the type of educational establishment. - Fedorenko E.O (Kharkov National Pedagogical University, 2011)
Considered and analysed influencing of features educational-organizational process on forming of priority lines of personality and level of motivation student to the specially organized motive activity. In experiment took part 101 senior pupils. Information of the questionnaire questioning in which students were determine the priority lines of personality and priorities during conducting of leisure is utillized in research. The presence of connections is certain between the level of motivation to the specially organized motive activity and lines personalities which student senior classes determine priority. It is proved that on intercommunication of lines of personality with the level of motivation to employments differences influence motive activity in organization of educational process of educational establishment.